2013
DOI: 10.1016/j.cytogfr.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptor trio: CXCR3, CXCR4 and CXCR7 crosstalk via CXCL11 and CXCL12

Abstract: Although chemokines are well established to function in immunity and endothelial cell activation and proliferation, a rapidly growing literature suggests that CXC Chemokine receptors CXCR3, CXCR4 and CXCR7 are critical in the development and progression of solid tumors. The effect of these chemokine receptors in tumorigenesis is mediated via interactions with shared ligands I-TAC (CXCL11) and SDF-1 (CXCL12). Over the last decade, CXCR4 has been extensively reported to be overexpressed in most human solid tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
188
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(192 citation statements)
references
References 99 publications
(144 reference statements)
1
188
1
2
Order By: Relevance
“…Briefly, the Transwell inserts were coated with Matrigel (1 mg/ml; BD Biosciences) or Col-I (1.2 mg/ml, Sigma-Aldrich; Merck KGaA, catalog no. SAB4200678), and allowed to gel at 37˚C for 1 h. Subsequently, A549 cells (3x10 5 ) in 200 µl serum-free Dulbecco's modified Eagle's medium (Biowest, Nuaillé, France) were added to the top of the Transwell. Serum-free medium was then added to the lower chamber and incubated for 24 h at 37˚C.…”
Section: Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, the Transwell inserts were coated with Matrigel (1 mg/ml; BD Biosciences) or Col-I (1.2 mg/ml, Sigma-Aldrich; Merck KGaA, catalog no. SAB4200678), and allowed to gel at 37˚C for 1 h. Subsequently, A549 cells (3x10 5 ) in 200 µl serum-free Dulbecco's modified Eagle's medium (Biowest, Nuaillé, France) were added to the top of the Transwell. Serum-free medium was then added to the lower chamber and incubated for 24 h at 37˚C.…”
Section: Antibodiesmentioning
confidence: 99%
“…CXC receptor 4 (CXCR4), considered as the only receptor of stromal-derived-factor-1 (also termed CXCL12), is an α-chemokine receptor (5). A number of studies have hypothesized that CXCR4 and CXCL12 increase the adhesive ability of tumors, as well as the degradation of the extracellular matrix (ECM) and basement membrane, which is beneficial to the invasion and metastasis of cancer cells (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The chemokine CXCL12 (stromal cellderived factor-1) and its receptor CXCR4 play a major role in invasion, proliferation, angiogenesis, and metastasis. Recently, CXCR7 was identified as an alternate receptor for CXCL12 and CXCL11/I-TAC (interferon-inducible T-cell a chemoattractant) [42,43]. Both IL-1b and K562R culture medium significantly increased the production of CXCL11, whereas K562S culture medium did not (Fig.…”
Section: Interaction Of Hs-5 Stromal Cells With K562r Cells Upregulatmentioning
confidence: 99%
“…The downstream intracellular signaling transduction pathways including Phosphatidylinositol 3-kinase (PI3K)/Akt/ mammalian target of rapamycin (mTOR), Rac1/extracellular signal-regulated kinase (ERK), mitogen-activated protein kinase (MAPK), p38MAPK, stress-activated protein kinase (SAPK), c-Jun N-terminal kinase (JNK)/ activator protein-1 (AP-1), Janus kinase/signal transducers and activators of transcription (JAK/STAT). 45,46 CXCR4 is the predominant chemokine receptor on human fibrocytes. More and more evidence have indicated that substantial numbers of CXCR4 + fibrocytes can migrate and accumulate in lung in response to CXCL12 during pulmonary fibrosis.…”
Section: Cxcl12/cxcr4 Axis Mediated Fibrocyte Trafficing In Pulmonarymentioning
confidence: 99%